Characterization of subthalamic nucleus deep brain stimulation evoked resonant neural activity in a large animal model: A pilot study - Hageman, Kristin; Stypulkowski, Paul; Stanslaski, Scott (Brain research, 2025)
[Display omitted] •STN DBS in healthy ovine animal model elicited evoked resonant neural activity (ERNA).•ERNA is present in chronically implanted animals for >2 yrs showing contact specificity.•ERNA amplitude is highly dependent on stimulation frequency due to phase interactions.•Frequency dependent behavior of ERNA was modeled by damped harmonic oscillator.•ERNA showed time dependent dynamics that settled at steady state. Recent reports have described stimulation evoked resonant neural activity (ERNA) recorded in the subthalamic nucleus (STN) and globus pallidus internus (GPi) of patients during Deep Brain Stimulation (DBS) surgery. The constraints imposed during intraoperative recordings in patients limit the opportunity for in-depth study of new findings such as ERNA. In this pilot study, we leverage a large animal model to focus on detailed characterization of ERNA. Bilateral DBS leads were implanted in the STN in three ovine subjects and externalized for chronic use with custom stimulation and recording circuitry. ERNA was reliably recorded from the STN region in all three subjects with distinct specificity to recording and stimulation sites/contacts. Basic neural response characteristics such as input/output behavior, frequency response and strength/duration curves were evaluated. ERNA amplitude was highly dependent upon stimulation frequency, due to the interaction of the underlying resonant activity and the evoked response from each stimulus pulse. The results could be predicted by a mathematical model of constructive/destructive phase interference, and importantly, the evoked response latency. Significant time dependent dynamics in these evoked potentials were observed, which will be critically important to understand for future clinical applications. Based upon these recordings from leads in the STN region of healthy ovine subjects, these data confirm that DBS evokes high frequency resonant activity in the basal ganglia network. The clinical utility of ERNA remains to be demonstrated, but its direct association with DBS therapy makes it an interesting biomarker for potential use in contact selection and closed loop therapy.